Current controversies in cholangiocarcinoma (2017)
ABSTRACT: Cholangiocarcinoma represents 10% of primary liver malignancies and accounts for less than 3% of all gastrointestinal malignant tumors, with an enormous geographical variation. This neoplasia can arise from the biliary tract epithelium or hepatic progenitor cells. Depending on the anatomic localization, it is classified into three subtypes: intrahepatic, perihilar and distal. This fact is one of the main difficulties, because there are many studies that indistinctly include the results in the management of these different types of cholangiocarcinoma, without differentiating its location and even including gallbladder cancer. There are many controversial points in epidemiology, liver transplantation as a treatment, limitations of different results by group and type of treatment, histological testing and chemotherapy. This is a narrative review about topics in cholangiocarcinoma. This article is part of a Special Issue entitled: Cholangiocytes in Health and Disease edited by Jesus Banales, Marco Marzioni, Nicholas LaRusso and Peter Jansen.